Glory In White: Analogi Arsitektur Hotel Majapahit Dalam Penciptaan Busana Dengan Classic Elegant Style - Amritha Gamaya; I Gede Mugi R; Dewa Ayu Putu Leliana Sari (Style : Journal of Fashion Design, 2021)
Majapahit Hotel Surabaya is one of the Dutch colonial legacy and also a historical place forSurabayan people. The pure white nuance and the mixed of Art Nouveau and Art Decoarchitecture style of the hotel makes the hotel has its own uniqueness. Through theanalogy theory, the shapes that can describe the Majapahit Hotel is its architecture andinterior such as crystal lamp, symmetrical, flag terrace as one of the iconic construction ofthe hotel, geometric, arc line and clasic elegant. Those shapes become the style in thisfashion artwork which processed and can realize the Ready to Wear, Ready to WearDeluxe, and Haute Cotour the fashion artworks, which has been considered based on theexisted element and tenet. The creative creation process uses Tjok Instri Ratna CoraSudharsana design method named "FRANGIPANI, The Secret Steps of Art Fashion" whichconsist of ten steps of design fashion planning process.